Identifikasi Senyawa Aktif dari Tumbuhan Hutan Berkhasiat Obat sebagai Inhibitor HMG-CoA Reductase - Rahmania, Shelly; Sulistiyani, Sulistiyani; Lelono, Arthur A (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Cardiovascular disease is a leading cause of death worldwide, hypercholesterolemia is one of the causes. Three medicinal forest plants are potential natural resources to be developed as cholesterol-reducing herbal product, but scientific informations on their mechanism is still limited. The objective of this research is to explore the potency of the leaf of Jati Belanda (Guazuma ulmifolia), Jabon (Antocephalus macrophyllus), and Mindi (Melia azedarach) as inhibitor of HMG-CoA reductase (HMGR), a key enzyme in the regulation of cholesterol biosynthesis. Samples were macerated in ethanol 96% and the filtrate was partitioned using n-hexane and chloroform to obtain the ethanolic flavonoid extract. The effect of each extracts on the HMG-CoA reductase activity were analyzed using HMGR assay kit. At concentration of 10 ppm the G.ulmifolia ethanolic extract showed the highest inhibitory activity as well as pravastatin control inhibitor. The phenolic content of the ethanolic extracts of G.ulmifolia, A.macrophyllus, and M.azedarach were: 11.00, 34.83, and 13.67 mg gallic acid AE/g dried leaves, respectively. The flavonoid content of the ethanolic extracts of G.ulmifolia, A.macrophyllus, and M.azedarach were: 0.22, 0.64, and 0.78 mg QE/g dried leaves, respectively. Interestingly, G.ulmifolia extract the lowest concentration of phenolic and flavonoid content. HPLC analysis showed that all samples contain quercetin at similiar small concentrations (6.7%, 6.6%, and 7.0% for G.ulmifolia, A.macrophyllus, and M.azedarach, respectively). This indicating other active compounds may play some roles in this inhibitory action on HMG-CoA reductase activity. Further identification using LC-MS/MS showed that G.ulmifolia flavonoid extract contained an unidetified coumpound with molecural weight of 380.0723 Da.